PARAMETERS OF DIRECTED SPLITTING OF ROCKS USING NON-EXPLOSIVE DESTRUCTIVE MIXTURES (NEDM) - SOLOVEI, ANDRII; SСHIPANOV, IGOR (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Efficient extraction of stone products at enterprises is possible under the condition of high-quality separation of monoliths with less loss of raw materials. Stone blocks should be divided into more or less structural levels. It is worth specifying the specific direction of division. For this, non-explosive destructive mixtures (NeDM) are used in mining practice. It is essential to understand what influence the massif characteristics have on the rock. The article states at which temperatures of the mountain massif non-explosive mixtures can be used, and when it is inappropriate. The material considers why it is necessary to take into account the anisotropic and orthotropic properties of the stone and, ultimately, what should be the optimal diameter of the holes and the time of chemical reactions in them. In addition, questions regarding the parameters of the non-explosive mixtures themselves are highlighted. Namely, what temperature of water to use for preparing NeDM and mixing it with other components. We are talking about what the pressure of the working mixture in the holes should be. During this time, the mixture will develop the greatest pressure, and directed splitting will occur. The article examines the dependence of the force of expansion of a non-explosive mixture on the diameter of the hole. The dependence of the expansion force on exposure time and temperature was also considered. We are talking about the pre-compression of the mixture and what is the fluidity of destructive mixtures. Issues of the optimal distance between the holes, and the use of insert plates in the holes, which help to carry out accurate splitting, are highlighted. The ratio of uniform forces that load the walls of the hole is taken into account. It is shown under which conditions the formation of cracks is more likely and along which axes. The paper considers the influence of the anisotropic and orthotropic properties of rocks.
Keywords: directional splitting; cracking; non-explosive destructive mixtures; NeDM; mixtures pressure; rock temperature; hole diameters; anisotropy; orthotropy; isotropy; and insert plates